PENERAPAN PRINSIP KEHATI-HATIAN DALAM MEMBUAT AKTA JUAL BELI BERDASARKAN PERJANJIAN PINJAM NAMA - Ferbiano Geraldi Putra (JOURNAL SAINS STUDENT RESEARCH, 2024)
Verbal agreements are often encountered in everyday life such as at the market, in shops and so on. It can be said that verbal agreements usually occur in simple agreements. However, the problem is when verbal agreements are used in agreements that can cause major losses for the parties and enter the court. There are two problem formulations, one is how to apply the precautionary principle in making a sale and purchase deed based on nominee agreement? two, what are PPAT's responsibilities regarding the Deed of Sale and Purchase based on nominee agreement? This research is normative research based on secondary data which is then processed descriptively qualitatively. In fact, making a sale and purchase deed based on a nominee agreement does not reflect the application of the precautionary principle by a PPAT because it can result in the failure to achieve legal protection. The principle of responsibility of PPAT adheres to the principle of responsibility based on error where the PPAT must be proven to have made a mistake in order to then be held responsible